2003
DOI: 10.1029/2003gl017136
|View full text |Cite
|
Sign up to set email alerts
|

The three‐dimensional solar wind around solar maximum

Abstract: [1] Ulysses is now completing its second solar polar orbit, dropping back down in latitude as the Sun passes through its post-maximum phase of the solar cycle. A mid-sized circumpolar coronal hole that formed around solar maximum in the northern hemisphere has persisted and produced a highly inclined CIR, which was observed from $70°N down to $30°N. We find that the speed maxima in the high-speed streams follow the same slow drop in speed with decreasing latitude observed in the large polar coronal holes aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
214
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(226 citation statements)
references
References 16 publications
11
214
1
Order By: Relevance
“…Ulysses measurements showed that the polar solar wind observed at the southern pole differed slightly but distinctly from the polar wind in the northern hemisphere (McComas et al 2003). First evidence of such asymmetry was pointed out by Bertaux et al (1996a) based on Lyman-α observations from Prognoz.…”
Section: Introductionmentioning
confidence: 91%
“…Ulysses measurements showed that the polar solar wind observed at the southern pole differed slightly but distinctly from the polar wind in the northern hemisphere (McComas et al 2003). First evidence of such asymmetry was pointed out by Bertaux et al (1996a) based on Lyman-α observations from Prognoz.…”
Section: Introductionmentioning
confidence: 91%
“…At solar minimum, slow, hot solar wind forms a relatively narrow band around the heliographic equator, while the fast, cool wind fills the midlatitude and polar heliosphere, whereas at solar maximum, the slow wind extends to much higher latitudes [McComas et al, 2003]. In this view the slow solar wind is collocated with the dipolar streamer belt, the region where open solar magnetic field lines from opposite polarity polar coronal holes converge to form the heliospheric current sheet.…”
Section: Introductionmentioning
confidence: 92%
“…Figure 1 shows that A He is clearly correlated to wind speed at solar minimum, and more loosely so throughout the solar cycle. The correlation between wind speed and heliographic latitude during solar minimum has been demonstrated using the first Ulysses fast latitude scan in 1994(McComas et al 2003 and references therein). The key observation here, however, stems from the fact that the wind speed is not perfectly determined by heliographic latitude.…”
Section: Effect Of the Solar Wind Expansion Profile On A Hementioning
confidence: 99%